The Effect of Knowledge Sharing and Empowerment on Employee Performance with Job Satisfaction as a Media: (A Study of Salatiga City Regional Secretariat Employees) - Ronaldo Goncalves; Endang Tjahningsih (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study aims to analyze and describe the influence of knowledge sharing and empowerment on job satisfaction among employees of the Salatiga City Regional Secretariat. This study aims to analyze and describe the influence of knowledge sharing, empowerment, and job satisfaction on employee performance at the Salatiga City Regional Secretariat. This study aims to analyze and describe how job satisfaction mediates the influence of knowledge sharing and empowerment on employee performance at the Salatiga City Regional Secretariat. This study used a quantitative approach, with a population of 123 employees at the Salatiga City Regional Secretariat. Data were processed using SPSS version 26 software. Data analysis used primary data in the form of a questionnaire. Data analysis techniques included respondent descriptions, variable descriptions, validity tests, reliability tests, F-tests, determination tests (R2), partial t-tests, and Sobel tests. The results show that knowledge sharing has a positive effect on employee job satisfaction at the Salatiga City Regional Secretariat. Empowerment has a positive effect on employee job satisfaction at the Salatiga City Regional Secretariat. Knowledge sharing has a positive effect on employee performance at the Salatiga City Regional Secretariat. Empowerment has a positive effect on the performance of Salatiga City Regional Secretariat employees. Job satisfaction has a positive effect on the performance of Salatiga City Regional Secretariat employees. Job satisfaction mediates the effect of knowledge sharing on the performance of Salatiga City Regional Secretariat employees. Job satisfaction mediates the effect of empowerment on the performance of Salatiga City Regional Secretariat employees.